Smooth muscle gap-junctions allow propagation of intercellular Ca(2+) waves and vasoconstriction due to Ca(2+) based action potentials in rat mesenteric resistance arteries - Borysova, Lyudmyla (Cell Calcium, 2018)
The role of vascular gap junctions in the conduction of intercellular Ca(2+) and vasoconstriction along small resistance arteries is not entirely understood. Some depolarizing agents trigger conducted vasoconstriction while others only evoke a local depolarization. Here we use a novel technique to investigate the temporal and spatial relationship between intercellular Ca(2+) signals generated by smooth muscle action potentials (APs) and vasoconstriction in mesenteric resistance arteries (MA). Pulses of exogenous KCl to depolarize the downstream end (T1) of a 3 mm long artery increased intracellular Ca(2+) associated with vasoconstriction. The spatial spread and amplitude of both depended on the duration of the pulse, with only a restricted non-conducting vasoconstriction to a 1 s pulse. While blocking smooth muscle cell (SMC) K(+) channels with TEA and activating L-type voltage-gated Ca(2+) channels (VGCCs) with BayK 8644 spread was dramatically facilitated, so the 1 s pulse evoked intercellular Ca(2+) waves and vasoconstriction that spread along an entire artery segment 3000 μm long. Ca(2+) waves spread as nifedipine-sensitive Ca(2+) spikes due to SMC action potentials, and evoked vasoconstriction. Both intercellular Ca(2+) and vasoconstriction spread at circa 3 mm s(−1) and were independent of the endothelium. The spread but not the generation of Ca(2+) spikes was reversibly blocked by the gap junction inhibitor 18β-GA. Thus, smooth muscle gap junctions enable depolarization to spread along resistance arteries, and once regenerative Ca(2+)-based APs occur, spread along the entire length of an artery followed by widespread vasoconstriction.